Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1021/nl902720v
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Thermal Conductivity in Nanoengineered Rough Ge and GaAs Nanowires

Abstract: We model and compare the thermal conductivity of rough semiconductor nanowires (NWs) of Si, Ge, and GaAs for thermoelectric devices. On the basis of full phonon dispersion relations, the effect of NW surface roughness on thermal conductivity is derived from perturbation theory and appears as an efficient way to scatter phonons in Si, Ge, and GaAs NWs with diameter D < 200 nm. For small diameters and large root-mean-square roughness Delta, thermal conductivity is limited by surface asperities and varies quadrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
105
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(116 citation statements)
references
References 26 publications
9
105
0
Order By: Relevance
“…The conductivity is found to be significantly lower in NWs than in bulk GaAs. Furthermore, our results confirm recent theoretical calculations by Martin et al [7].…”
supporting
confidence: 93%
See 2 more Smart Citations
“…The conductivity is found to be significantly lower in NWs than in bulk GaAs. Furthermore, our results confirm recent theoretical calculations by Martin et al [7].…”
supporting
confidence: 93%
“…The conductivity is found to be significantly lower in NWs than in bulk GaAs. Furthermore, our results confirm recent theoretical calculations by Martin et al [7].We use zincblende NWs grown by gallium-assisted molecular beam epitaxy, exhibiting very high structural quality [8] and diameters d between 150 and 170 nm. The facets belong to the {110} family and the NW axis corresponds to the [111] direction.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…24,25,26,27,28 The thermoelectric phenomenon can be utilized to harvest otherwise wasted thermal energy directly into electric power. To increase the thermoelectric efficiency, the thermal conductivity in NWs should be reduced, which can be realized through phonon confinement effects, 29,30,31,32 isotope doping, 33 surface roughness, 34,35,36 or non-planar (kinked) structures. 37 Shi et al suggested enhancing the thermoelectric efficiency through gallium doping, and the thermoelectric figure of merit was found to be increased by a factor of 2.5 at 4% gallium doping.…”
Section: Introductionmentioning
confidence: 99%
“…6 Although, some/many aspects of the thermal and electrical transport maybe considered to be independent of the exact fabrication process implemented, two important scattering mechanisms which can depend on the exact nature of the quality of the epitaxial growth are interface roughness and dislocation scattering, these two mechanisms are related to some degree. 7,8 roughness scattering on thermal conductivity has been studied previously, 9,10 although little has been done in the context of thermoelectrics directly where it is important to consider both electrical and thermal transport. However, for strain-balanced multiple quantum well superlattices, the formation of a number of threading edge dislocations is inevitable and dislocations are likely to play a dominant role, in determining the feasibility of such structures.…”
mentioning
confidence: 99%